How Can Preachers Use Luther in a Decolonial Multicultural Context? - Leitzke, Timothy (Religions, 2024)
This article seeks a way for preachers to use Martin Luther’s theology today without succumbing to Luther’s anti-Semitism. Its place in the discipline of homiletics is of hermeneutics and general sermon direction. I argue that Luther’s anti-Semitism is theological, and that in order to avoid anti-Semitism, Luther’s theology must be changed. I also argue that the concept of decoloniality offers a way forward, specifically in hybridizing Luther’s theology in today’s world.